Lived Experiences of Senior High School Learners Under the Online Learning Mode at Goshen School of Technology and Humanities - Cruz, Kyle Dela; Raagas, Joenessa Mae D.; Maming, Jimmy B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Covid-19 impacted all sectors of the country particularly the education sector. Schools have no choice but to shut their operations from brick and mortar to flexible learning mode. This study intends to determine the lived experiences, the issues they have encountered, the support needed, and the gaps and challenges they are facing. This study utilized interviews, observations and used Collaizi's method in the data processing and analysis (cited in Sander, 2003, and Speziale & Carpenter, 2007). The themes that came out from the constructs of the interviewees were Learners under online learning mode encountered internet connectivity issues, inadequate learning tools for online, psychological issues, and physical health issues. The output of this paper is the proposed model for learners under online the learning.